PENGARUH LEVERAGE, INTENSITAS ASET TETAP, UKURAN PERUSAHAAN, DAN KONEKSI POLITIK TERHADAP TAX AVOIDANCE - Dharma, I Made Surya; Ardiana, Putu Agus (E-Jurnal Akuntansi, 2016)
This study aimed to examine the effect of leverage, the intensity of fixed assets, the size of the company, and the political connections against tax avoidance. Measurement of tax avoidance in this study using the effective tax rate (ETR). This study was performed on companies listed in the Indonesia Stock Exchange (BEI) 2012-2014. The number of observations of 144 sample obtained by the method nonprobability sampling purposive sampling technique. The analysis technique used in this research is multiple linear regression analysis. The analysis showed that the intensity of a fixed asset leverage and negative effect on tax avoidance. This shows that the higher leverage and intensity of fixed assets will lead to reduced levels of tax avoidance. Company size has positive influence on tax avoidance. This means that the higher the size of the company, the tax avoidance measures will be high. While political connections did not affect the tax avoidance measures.
Keywords: Tax Avoidance, Leverage, Intensity Fixed Assets, Company Size, Political Connections